Effect of Probiotic Bacteria of Bacillus Subtilis Strain BR2CL or Bacillus sp. strain BT3CL to Broiler Performance - R. A., Sinta Dewi; Mahardika, I G.; Mudita, I M. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the performance of broiler given probiotics Bacillus subtilis strain BR 2 CL and Bacillus sp. strain BT 3 CL. The research was carried out for 2 months at Tajen Village, Penebel, Tabanan, Bali and continued with the sample analysis at the Animal Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University. This study used completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatments were broiler without additional probiotic inoculant (A), Broiler with additional probiotic bacteria Bacillus sp.strain BT 3 CL through of drinking water (B), broiler were given additional probiotic bacteria Bacillus subtilis strain BR 2 CL through of drinking water (C) and broiler were given additional probiotic bacterial mixed Bacillus sp.strain BT 3 CL and Bacillus subtilis strain BR 2 CL through of drinking water (D). The observed variables is feed consumption, water consumption, initial body weight, final body weight, daily body weight gain and feed conversion. The results showed that the adding of inoculants probiotic bacteria Bacillus sp. strain BT 3 CL ( B), Bacillus subtilis strain BR 2 CL (C) and mixture of Bacillus sp. strain BT 3 CL and subtilis strain BR 2 CL through drinking water (D) significantly (P<0,05) increase ration consumption, water consumption, body weight gain, and final body weight than broiler that get treatment A. While feed conversion values ??are real (P <0,05) lower than broiler that received treatment A. Based on this it can be concluded giving as much as 50 ml of inoculant into 1 liter of drinking water Bacillus subtilis strain BR 2 CL or Bacillus sp. strain s BT 3 CL can improve the appearance of broiler. Keywords: Broiler, Bacillus sp. strain BT 3 CL, Bacillus subtilis strain BR 2 CL